Guazuma Ulmifolia Lamk Leaf Tea to Decrease Blood Lipid Profiles in Depo-Medroxyprogesterone Acetate (DMPA) Acceptors - Mimi Ruspita; Khobibah Khobibah; Tri Nur Hidayati; Rozikhan Rozikhan (Poltekkes Kemenkes Surakarta, 2025)
Background: Depo Medroxyprogesterone Acetate (DMPA) is an injectable contraceptive method that is widely used in Indonesia and has the side effect of increasing the blood lipid profile. Guazuma ulmifolia Lamk. leaf has been proven to have benefits in controlling blood lipid levels. However, in previous research, giving Guazuma ulmifolia Lamk. leaves was mostly done only on experimental animals. It is important to measure changes in blood lipid levels of cholesterol, LDL, HDL and triglycerides after consuming guazuma ulmifolia lamk leaf in DMPA acceptor. Methods: Quasi-experiment with one group pretest-posttest design, with 48 respondents using purposive sampling. The intervention was carried out for 10 days routinely, twice a day, by giving 2 grams of Guazuma ulmifolia Lamk leaf tea. Analyse data of cholesterol levels and HDL levels using the T-test, while LDL and triglyceride levels using the Wilcoxon signed ranks test. Results: There was a decrease in cholesterol levels (p-value = <0.001) and a decrease in LDL levels (p-value = <0.001), but it was not proven to increase HDL levels (p-value = 0.185) and decrease triglyceride levels (p-value = 0.353). Conclusion: Giving guazuma ulmifolia lamk leaf tea was effective in decreasing cholesterol levels and decreasing LDL levels of DMPA acceptors. It is hoped that health workers can provide guazuma ulmifolia lamk leaf tea as an alternative or additional medicine to reduce cholesterol levels due to the side effects of DMPA injections.